Culture shock level among nursing students during their clinical education - Aulia Fauzia Masroorianissa; Ida Maryati; Furkon Nurhakim; Suharjiman Suharjiman (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Culture shock not only induces stress but also fatigue, This is primarily due to the frequent exposure with new cultures when moving between different hospital practice locations, potentially affecting the quality of nursing care provided.Purpose: To determine culture shock level during clinical education of professional nursing student.Method: This research was conducted on 158 students of the Nursing Profession Program at Jenderal Achmad Yani University utilized a total sampling technique with 127 participants (80%) completing the Mumford Culture Shock Questionnaire in accordance with the principle of sample adequacy. The validity test results were 30 valid items and 8 invalid items, while the reliability test results demonstrating high reliability with elevated alpha values for all 30 items. Ethics obtained from the Ethics Committee of 'Aisyiyah Bandung University. The data were analyzed univariately through frequency distribution.Results: Non-regular classes tend to have a low level (60%) due to the contrasting background between working non-regular students and non-working regular students. Women tend to have moderate culture shock levels (93.4%) whereas men show lower levels (11.8%). The majority of students are 23 years old and have all culture shock levels. In terms of ethnicity, most non-Sundanese student, have a moderate culture shock level influenced by language disparities. Socio-demographic conditions consisting of gender, age, and ethnicity play a role in differences in the culture shock level experienced by respondents. There are six aspects that play a role in the culture shock experienced by respondents.Conclusion: The culture shock experienced by professional nursing students is more at the low and medium levels, indicating a spectrum of adaptability among the student body and there are many students who still have difficulty adapting to the new environment.